2020
DOI: 10.1097/inf.0000000000002829
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Tract Infection in Febrile Infants With Upper Respiratory Tract Symptomatology

Abstract: Among 439 infants presenting with symptoms of upper respiratory tract infection and temperature ≥39°C, 19 (4.3% [95% confidence interval, 2.8–6.7]) received a diagnosis of urinary tract infection (abnormal urine dipstick from a sterile urine sample and positive urine culture). Regardless of respiratory presentation, all infants presenting with a temperature of 39°C should be screened for urinary tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…11 However, a prospective cohort study from Spain including 439 infants with upper respiratory tract symptoms reported that 19 (4.3%) were diagnosed with febrile UTI. 8 Several studies from the United States showed that the incidence of UTI in febrile infants with bronchiolitis ranged from 4.5% to 7.7% and was highest in female or uncircumcised male patients. [12][13][14] Considering the results in our study, where all patients were female or uncircumcised male infants, clinicians should consider UTI in febrile infants with risk factors for UTI, even if they have respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, a prospective cohort study from Spain including 439 infants with upper respiratory tract symptoms reported that 19 (4.3%) were diagnosed with febrile UTI. 8 Several studies from the United States showed that the incidence of UTI in febrile infants with bronchiolitis ranged from 4.5% to 7.7% and was highest in female or uncircumcised male patients. [12][13][14] Considering the results in our study, where all patients were female or uncircumcised male infants, clinicians should consider UTI in febrile infants with risk factors for UTI, even if they have respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…7 Infants 2–24 months of age who were diagnosed with “urinary tract infection” in the DPC data from March 1, 2012, to May 31, 2023, and who were admitted to the general pediatrics department were found using a search engine of DPC data. We further selected cases that met all the following diagnostic criteria of febrile UTI 8,9 : (1) pyuria on urinalysis obtained in the ED (defined as more than 5 white blood cells per high-power field); (2) isolation of at least 10 4 colony forming units per milliliter of single uropathogens from a urine culture obtained by catheterization; (3) body temperature greater than or equal to 38 °C measured in the ED or by caregivers within the 24 hours before the presentation.…”
Section: Methodsmentioning
confidence: 99%
“…14 Nonetheless, a prospective cohort study from Spain of 439 infants (male, <12 months; female, <24 months) with upper respiratory tract symptoms found 19 (4.3%) were diagnosed with UTI. 15 In a single-centre study from the United States of 90 febrile infants (2 to 12 months of age) with clinically diagnosed bronchiolitis, 4 (4.4%) were diagnosed with UTI. 16 This study was subsequently expanded to a prospective, multicentre cohort study of 442 patients with clinically diagnosed bronchiolitis and found that 33 (7.5%) had a concomitant UTI.…”
Section: Infants 2 To 24 Months Of Agementioning
confidence: 99%
“…Previous data of febrile infants showed a non-negligible prevalence also in older patients, even though they had viral symptoms. 55 On the other hand, a meta-analysis of UTI and bronchiolitis revealed a lower prevalence of UTI when a strict criterion for diagnosis was established. 56 In our study, the prevalence of UTI was below 1%, although the variation in UTI prevalence between studies was much greater than that found between IBIs.…”
Section: Systematic Reviewmentioning
confidence: 99%